Infective endocarditis in an intravenous drug user: multiple fatal complications - Hughes, Hannah L (BMJ Case Rep, 2021)
Here, we present a case of a 43-year-old patient with a background of active intravenous drug use who was diagnosed with aortic valve endocarditis. This was complicated by extensive acute embolic stroke and acute splenic, renal and liver infarction. This case highlights the difficulties in managing infective endocarditis in intravenous drug users and the importance of a comprehensive approach, addressing both the intracardiac infection and the underlying issue of substance misuse, to ensure best patient outcomes.